Desempenho ocupacional de crianças no transtorno do espectro autista e compreensão das mães após a terapia ocupacional assistida por cães - Roiz, Roberta Giampá (Universidade Federal de São Carlos, 2026)
Canine-Assisted Occupational Therapy has been practiced worldwide, producing literature on its effectiveness for different populations. It is an innovative, client-centered approach, with objectives achieved through a relationship established between the child and the dog, which collaborates in engaging the child in therapy. This process involves a methodology, requirements for therapists and dogs, and session planning based on objectives established for each child, previously assessed and periodically reassessed. This study aimed to evaluate and describe, from the perspective of mothers of children on Autism Spectrum Disorder (ASD) who underwent Canine-Assisted Occupational Therapy, whether there was a change in their children's occupational performance and whether the intervention impacted maternal burden, as well as their understanding of this therapeutic modality. This is a quasi-experimental study of the program evaluation type, with the application of pre- and post-test measures. The sample consisted of 4 children on ASD and their respective mothers. To assess the children's occupational performance, the Canadian Occupational Performance Measure (COPM) was used, which was completed by the mothers. The Zarit Burden Scale was used to assess workload, and a semi-structured interview guide was used to understand the therapy. Data analysis adopted a quantitative-qualitative approach, with the standardized instruments having their own analysis procedures for obtaining scores, and the results expressed in tables, charts, and graphs. The analysis of the interview responses was conducted using thematic analysis as proposed by Braun and Clarke, and the Taguette software was used to generate the initial codes. Among the results, the children's ages ranged from 3 to 9 years, with 2 boys and 2 girls on ASD, and the duration of treatment in Canine-Assisted Occupational Therapy ranged from 4 to 6 months. Regarding the children's characteristics, they generally presented with selective eating, psychomotor agitation, stereotypies, communication difficulties, attention and concentration problems, and restricted social interaction. Regarding functional problems affecting occupational performance, difficulties included holding/handling/delivering objects, verbalization, attention, concentration, sitting, social interaction, bathing, dressing, tying shoelaces, gripping pencils and scissors, self-esteem, and kicking a ball. Based on the children's functional problems affecting occupational performance, therapeutic plans were developed and implemented for each child, incorporating the dog in an active or indirect way. Regarding changes in occupational performance, one of the four children did not show a significant change according to the score established by COPM. Each mother expressed her unique understanding of Canine-Assisted Occupational Therapy based on the changes they considered positive in their children's occupational performance. Regarding the level of maternal burden, in the pre- and post-intervention comparison, all showed good changes in their burden levels. It is concluded that Canine-Assisted Occupational Therapy is a promising and humanized intervention that contributes to the development of children on ASD and to the well-being of their families.
Occupational performance of children on autism spectrum disorder and mothers' understanding after canine-assisted occupational therapy
Keywords: Serviços Assistidos por Animais; Terapia Assistida por Animais; Terapia Ocupacional Assistida por Cães; Transtorno do Espectro Autista; Desempenho Ocupacional; Animal-Assisted Services; Animal-Assisted Therapy; Canine-Assisted Occupational Therapy; Autism Spectrum Disorder; Occupational Performance; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar